2018
DOI: 10.3233/jad-170970
|View full text |Cite
|
Sign up to set email alerts
|

Linking Atrial Fibrillation with Alzheimer’s Disease: Epidemiological, Pathological, and Mechanistic Evidence

Abstract: Many studies have shown a relationship between atrial fibrillation (AF) and vascular dementia. AF is a major risk factor for stroke, and stroke is the greatest risk factor for vascular dementia. However, the relationship between Alzheimer’s disease (AD), the leading cause of dementia, and AF remains unclear. At least four epidemiological studies have reported AF significantly raises the risk of AD 1.5- to 2.5-fold. Chronic cerebral hypoperfusion, resulting from persistent AF, could explain the link as hypoperf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 60 publications
4
42
0
6
Order By: Relevance
“…We provide an approach to interpret the data from mechanistic studies based on microbiome. The microbiome features revealed a close association of AF with neurodegenerative diseases as well as cancers, which was supported by prior studies showing that AF had correlation with AD and PD 52, 53 , and AF patients had relatively higher risks of several cancers including lung cancer and CRC 54, 64 . We also observed that microbiome features of SLE and CML were highly similar.…”
Section: Discussionsupporting
confidence: 75%
“…We provide an approach to interpret the data from mechanistic studies based on microbiome. The microbiome features revealed a close association of AF with neurodegenerative diseases as well as cancers, which was supported by prior studies showing that AF had correlation with AD and PD 52, 53 , and AF patients had relatively higher risks of several cancers including lung cancer and CRC 54, 64 . We also observed that microbiome features of SLE and CML were highly similar.…”
Section: Discussionsupporting
confidence: 75%
“…The incidence of SS has been reported to be related to sheath management, anticoagulation strategy, lesion site, ablation energy source, and intra‐cardiac cardioversion 41 . A previous report suggested that the SS was associated with the development of dementia and poor neuropsychological prognosis 42 . In addition, brain biopsy results from animal model studies showed that even healed lesions, based on MRI findings, leave behind evidence of cerebral ischaemic injury 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Persistent AF reduces cardiac output and may lead to chronic cerebral hypoperfusion and hypoxia, which may impair the clearance and promote the accumulation of amyloid-beta peptides in cerebral vessels, thus leading to cerebral amyloid angiopathy and contributing to the onset of Alzheimer’s disease (AD) [ 37 39 ]. However, this hypothesis has been investigated by very few studies, among which one study examined the cognitive function and cerebral blood flow velocity in the major brain arteries in 187 patients with heart failure, out of which 32% had a history of AF [ 40 ].…”
Section: Association Of Atrial Fibrillation With Cognitive Decline Anmentioning
confidence: 99%